Particulate Matter Sources Geoinformatics Identification Within Black Carbon Arctic Penetration Management - Valery M. ABRAMOV; Vladimir A. BOLSHAKOV; Vyacheslav G. BURLOV; Eugene P. ISTOMIN; Yaroslav A. PETROV; Oleg I. SHEVCHUK; Evgeniy A. BAIKOV; Mikhail B. SHILIN; Igor A. SIKAREV; Oksana PETRIEVA (Communications of International Proceedings, 2021)
The article considers geoinformatics identification of particulate matter sources within Black Carbon Arctic Penetration Management during Industry 4.0 period. It is recommended to use the digital online platforms, which integrate heterogeneous hardware and software resources with the use of web-technologies in the distributed networks to increase the efficiency and reliability of geoinformatics identification. As study results, there are demonstrated some examples for Russian Arctic. The research results have significant scientific novelty and can be useful for the state environmental control bodies and the public environmental organizations of the civil sector. Platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for the preliminary discussion and data exchange while research.
Keywords: geoinformatics identification; particulate matter; black carbon; Arctic